2010
DOI: 10.1016/j.foreco.2010.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Does afforestation increase bird nest predation risk in surrounding farmland?

Abstract: a b s t r a c tAfforestation of agricultural land is increasingly used to deliver environmental benefits, but their effects on biodiversity remain poorly understood. This paper tests the hypothesis that afforestation changes predation processes in surrounding farmland, examining how the characteristics and landscape context of forest plantations affect predator (birds and mammalian carnivores) and key prey (rabbits and hares) abundances, and bird nest predation rates in Iberian cereal-steppes. Lagomorphs and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 70 publications
(110 reference statements)
2
44
0
Order By: Relevance
“…The existence of these large amounts of natural vegetation within plantations was widely used as environmental propaganda by the pulpwood industry, which merchandised them as 'conservation' areas. Recent studies have shown that the conservation value of these 'ecological networks' for grassland species is greatly limited, mostly because of habitat unsuitability (Lipsey & Hockey, 2010) and high rates of nest predation (Reino et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of these large amounts of natural vegetation within plantations was widely used as environmental propaganda by the pulpwood industry, which merchandised them as 'conservation' areas. Recent studies have shown that the conservation value of these 'ecological networks' for grassland species is greatly limited, mostly because of habitat unsuitability (Lipsey & Hockey, 2010) and high rates of nest predation (Reino et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We analysed all possible models (2 n , where n is the number of variables), using MuMIn library in R (Bartoń 2013, Hastie & Tibshirani 1990. Although this approach is criticized, the analysis of all possible models is often used when there is not enough a priori information to develop a small set of models (Whittingham et al 2005, Reino et al 2010. To reduce the possibility of finding spurious models, we used only dominant uncorrelated habitat variables selected by their VIF from the initial large set of variables (see also Reino et al 2010).…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…Although this approach is criticized, the analysis of all possible models is often used when there is not enough a priori information to develop a small set of models (Whittingham et al 2005, Reino et al 2010. To reduce the possibility of finding spurious models, we used only dominant uncorrelated habitat variables selected by their VIF from the initial large set of variables (see also Reino et al 2010). The probability of including a variable in the best parsimonious model was estimated as relative importance (RI) by summing the Akaike weights of all candidate models in which the variable was included (Burnham & Anderson, 2002, Reino et al 2010.…”
Section: Data Processing and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We analysed all possible models (2 n , where n = number of variables), using MuMIn library in R (Hastie and Tibshirani 1990;Barton´2013). Although this approach is criticized, the analysis of all possible models is often used when there is not enough a priori information to develop a small set of models (Whittingham et al 2005;Reino et al 2010). The probability of including a variable in the best parsimonious model was estimated as the relative importance (RI) by summing the Akaike weights of all candidate models in which the variable was included (Burnham and Anderson 2002;Reino et al 2010).…”
Section: Data Processing and Analysismentioning
confidence: 99%